APOE ϵ4 increases the risk of progression from amnestic mild cognitive impairment to Alzheimer's disease among ethnic Chinese in Taiwan. Issue 2 (26th July 2010) - Wang, Pei-Ning; Hong, Chen-Jee; Lin, Ker-Neng; Liu, Hsiu-Chih; Chen, Wei-Ta
Abstract : Objective: To evaluate the effect of the apolipoprotein E (APOE) ϵ4 in the progression from mild cognitive impairment (MCI) to Alzheimer's disease (AD) in ethnic Chinese people in Taiwan. Methods: Subjects older than 60 years with normal cognition, MCI or AD were enrolled from the memory clinic from 2000 to 2008. Normal ageing and MCI subjects were evaluated with clinical and neuropsychological examinations annually, and their APOE genotypes were determined. Results: A total of 326 normal ageing subjects, 304 amnestic MCI and 537 AD patients were recruited at baseline. The frequencies of APOE ϵ4 were 22.1% in normal ageing, 26.6% in MCI and 40.8% in AD patients. During the follow-up period (42.5±18.5 months), there were 227 MCI patients, and 248 normal ageing subjects received one or more annual follow-up evaluation. The ϵ4+carriers had a higher annual conversion rate than did the ϵ4-negative subjects either in the MCI (15.9% vs 9.0%) or in the normal ageing subjects (2.2% vs 0.7%). The mean survival time before progression to AD was 57.0 months for the MCI ϵ4+carriers, 85.9 months for MCI ϵ4-negative patients, 86.2 months for normal ageing e4+carriers and 120.8 months for normal ageing ϵ4-negative subjects. The adjusted hazard ratio of APOE ϵ4 for developing AD was 2.0 (95% CI 1.2 to 3.2) in MCI and 5.3 (95% CI 1.2 to 24.1) in normal ageing. Conclusion: APOE ϵ4 increased the risk of developing AD both in amnestic MCI and in normal ageing in a clinic-recruited ethnic Chinese population.